(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article examines the emerging opportunities for tourism in Uzbekistan, focusing on key sectors such as cultural tourism, eco-tourism, adventure tourism, and wellness tourism. It provides an in-depth analysis of how Uzbekistan’s rich historical heritage, diverse landscapes, and strategic government initiatives are shaping the future of the tourism industry. Through a mixed-methods approach, including surveys, interviews, and secondary data analysis, the article highlights the country’s potential to attract international tourists. The study identifies critical factors such as infrastructure development, sustainability, and cultural preservation that can drive tourism growth. It also discusses the challenges facing the sector, such as the need for improved services and better connectivity. The findings suggest that Uzbekistan’s tourism sector is poised for growth, provided it can leverage its unique cultural and natural resources, while modernizing its infrastructure and services.